Political identification in Europe : community in crisis? - Machin, Amanda; Meidert, Nadine (Emerald Publishing, 2021)
In recent years, Europe has been buffeted by a series of contested crises that seemingly undermine and overwhelm its institutions and ideals: the economic shocks of 2008, the open disputes over migration, the political uncertainty generated by Brexit and the inroads made by various populist and nationalist parties into government.